The Implementation of Product Marketing Strategy of PT. Asuransi Umum Bumi Putera Muda 1967 at Dumai Branch - aditiya, variza (Jurnal Niara, 2020)
The purpose of this study was to see the implementation of the marketing strategy of PT. Asuransi Umum Bumi putera Muda 1967 at Dumai Branch. The theory used is according to Lovelock, namely: Product, Price, Place, Promotion, People, Physical Evidence and Process. This study uses a combined research method that is using descriptive methods with a quantitative approach. Types and sources of data in this study are primary data and secondary data. Data collection techniques used were questionnaires and interviews. Data analysis was performed using descriptive statistical analysis techniques. One of the sampling techniques used in determining individual samples is purposive random sampling. The results of 97 respondents showed that respondents' attitudes about the Marketing Strategy variable based on the calculation of the total questionnaire score were in the Good category with a score of 7,985 with a percentage of 74.83%. Analysis of respondents' attitudes about Product Marketing Strategy Analysis at PT. Asuransi Umum Bumi putera Muda 1967 at Dumai Branch showed a positive attitude. The factors that influence the Product Marketing Strategy at PT. Asuransi Umum Bumi putera Muda 1967 at Dumai Branch is Lack of utilization of the use of brochures, Lack of socialization in following the expo and the many requirements in matters of claims and Lack of certainty of time in service.